Future prospects of 2D materials for sensing applications - Morgan, Hywel; Rout, Chandra S.; Late, Dattatray J. (Fundamentals and Sensing Applications of 2D Materials, 2019)
Two-dimensional (2D) material attracted significant research interest from the discovery of graphene in 2004. These 2D materials allow a platform for artificial integration of heterostructures with unique platforms that show exotic physical attributes and phenomenon as well as properties and applications. Each layer in 2D materials consist of a covalent bond, a dangling bond-free lattice, and weak van der Waals (vdWs) interaction. This makes it feasible to fabricate lateral and vertical vdWs heterostructures without the constraints of lattice matching and processing compatibility. These vdWs heterostructures open a door for a broad range of applications in electronics, optoelectronics, flexible devices, sensors, and photovoltaics. In this chapter, we have critically assessed the recent developments in 2D materials, the fabrication of heterostructures, and their application for sensing purposes. We conclude with current challenges and ideas concerning future developments in this merging field.